2021
DOI: 10.3389/fcell.2021.626619
|View full text |Cite
|
Sign up to set email alerts
|

Exometabolomic Analysis of Decidualizing Human Endometrial Stromal and Perivascular Cells

Abstract: Differentiation of endometrial fibroblasts into specialized decidual cells controls embryo implantation and transforms the cycling endometrium into a semi-permanent, immune-protective matrix that accommodates the placenta throughout pregnancy. This process starts during the midluteal phase of the menstrual cycle with decidual transformation of perivascular cells (PVC) surrounding the terminal spiral arterioles and endometrial stromal cells (EnSC) underlying the luminal epithelium. Decidualization involves exte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 77 publications
1
12
0
Order By: Relevance
“…et al investigated the exometabolome of decidualizing human stromal cells in culture and concluded that the metabolic footprints of cellular microenvironment generated by different decidual subpopulations encode spatiotemporal information that may be important for their differentiation and optimal embryo implantation. It has been shown that in all investigated timepoints of decidualization the most enriched metabolic pathways of stromal cells exometabolome are phenylalanine, tyrosine and tryptophan biosynthesis, valine, leucine, and isoleucine biosynthesis, glycerophospholipid metabolism, linoleic acid metabolism, purine and pyrimidine metabolism [ 72 ]. It is interesting to note, that the similar pathways were enriched after analysis of day 5 human embryo exometabolome in our study.…”
Section: Discussionmentioning
confidence: 99%
“…et al investigated the exometabolome of decidualizing human stromal cells in culture and concluded that the metabolic footprints of cellular microenvironment generated by different decidual subpopulations encode spatiotemporal information that may be important for their differentiation and optimal embryo implantation. It has been shown that in all investigated timepoints of decidualization the most enriched metabolic pathways of stromal cells exometabolome are phenylalanine, tyrosine and tryptophan biosynthesis, valine, leucine, and isoleucine biosynthesis, glycerophospholipid metabolism, linoleic acid metabolism, purine and pyrimidine metabolism [ 72 ]. It is interesting to note, that the similar pathways were enriched after analysis of day 5 human embryo exometabolome in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Harden et al. showed significant differences in endometrial metabolic profiles between decidualized and nondecidualized endometrium, which may be essential for successful embryo implantation ( 46 ).…”
Section: Omics Studies Investigating the Establishment And Maintenanc...mentioning
confidence: 99%
“…The samples were analyzed using an Agilent 1290 ultrahigh pressure liquid chromatography system (Agilent, Waldbronn, Germany) equipped with a 6550 iFunnel Q-TOF mass detector managed by a MassHunter Workstation, as previously described. 48,49 A Waters ACQUITY UPLC HSS T3 (2.1 Â 100 mm, 1.8 mm; Waters, Milford, MA, USA) column was used with a Waters ACQUITY HSS T3 1.8 mM VanGuard guard column. The column temperature was 50 C. The separation was performed under a gradient elution which involved a mobile phase consisting of (A) 0.1% formic acid in water and (B) 0.1% formic acid in methanol.…”
Section: Untargeted Metabolomics Analysis By Lc-msmentioning
confidence: 99%